2004
DOI: 10.1002/jemt.20014
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in the nervous and endocrine control of the thymus

Abstract: The immune system, especially the thymus, undergoes age-related modifications leading to structural and functional changes in the lymphoid organs and immunocompetent cells. Nevertheless, the consequences of thymic involution in the peripheral pool of T-cells are still a matter of controversy. The control of the thymic function is very complex and involves intrathymic signals, the autonomic nervous system, and the endocrine system. Both thymocytes and thymic stromal cells express receptors for a wide range of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Beyond doubt, the age-dependent variations in activity of individual subpopulations of TEC are quite complex, controlled in response to growth factors, locally formed in various thymic compartments, modulated by a great variety of neural, endocrine factors of extrathymic origin (for review see Garcia-Suarez et al 2003;Hannestad et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond doubt, the age-dependent variations in activity of individual subpopulations of TEC are quite complex, controlled in response to growth factors, locally formed in various thymic compartments, modulated by a great variety of neural, endocrine factors of extrathymic origin (for review see Garcia-Suarez et al 2003;Hannestad et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(1) a decreased pool of hematopoietic precursors of thymocytes and inhibited process of thymocyte differentiation (Aspinall 2003;Min et al 2004), (2) alterations in the neuroendocrine control of the thymus, as well as in levels of locally acting growth factors, including cytokines and thymic hormones (Garcia-Suarez et al 2003;Hannestad et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of peripheral T-cell numbers appears to be regulated via a thymus-independent homeostatic process involving expansion of mature peripheral T cells which results in a much more limited T-cell receptor (TCR) repertoire with age. While the precise mechanism(s) facilitating thymic involution has yet to be determined, it appears that this thymic loss is an active process involving a variety of factors including the loss and apoptosis of the thymocytes and supportive cell populations within the microenvironment, alterations in the appropriate signals from supporting stromal and epithelial cells, diminished progenitor cell recruitment and expansion and a decrease in steroid signaling essential for thymocyte development 17-25. Other factors which are yet to be identified may also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the thyroid hormone T 3 modulates the thymic microenvironment, enhancing thymic endocrine function (as exemplified by thymulin secretion), as well as ECM production and ECM receptor expression, with consequent augmentation of in vitro thymocyte adhesion [2,9,[25][26][27]. Accordingly, we also showed the presence of nuclear T 3 receptors in thymocytes and various preparations of thymic microenvironmental cell types [26,28].…”
Section: Introductionmentioning
confidence: 61%